Proving f (f bool) = bool

Posted by Marcus Whybrow on Stack Overflow See other posts from Stack Overflow or by Marcus Whybrow
Published on 2009-11-04T14:18:00Z Indexed on 2010/03/13 10:45 UTC
Read the original article Hit count: 537

Filed under:
|

How can I in coq, prove that a function f that accepts a bool true|false and returns a bool true|false (shown below), when applied twice to a single bool true|false would always return that same value true|false:

(f:bool -> bool)

For example the function f can only do 4 things, lets call the input of the function b:

  • Always return true
  • Always return false
  • Return b (i.e. returns true if b is true vice versa)
  • Return not b (i.e. returns false if b is true and vice vera)

So if the function always returns true:

f (f bool) = f true = true

and if the function always return false we would get:

f (f bool) = f false = false

For the other cases lets assum the function returns not b

f (f true) = f false = true
f (f false) = f true = false

In both possible input cases, we we always end up with with the original input. The same holds if we assume the function returns b.

So how would you prove this in coq?

Goal forall (f:bool -> bool) (b:bool), f (f b) = f b.

© Stack Overflow or respective owner

Related posts about homework

Related posts about coq